Precarização do trabalho e saúde dos magistrados trabalhistas no Brasil (2003 - 2014) - Nogueira, Thayse Palmela [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Our objective was to investigate the work of righteousness production conditions in Brazil and its impacts on the health of the labor judiciary from 2003 to 2014, a period that marks the beginning of the Constitutional Amendment number 45/2004, which caused significant changes in the Brazilian Judiciary in particular in the labor courts, which was expanded competence, through the new wording given to art.114 of the Federal Constitution. In these ten years of the judicial modernization, chatty modernization permeated by business logic, there was the introduction of informational-organizational technologies, in addition to the management shock, which is nothing but the electronic court case coupled to Toyotist management. In this transition process, the judges of first instance of the Labor Court failed to report the dimensions of the work precariousness and health through interviews and empirical data collection. With the data, we found that the profile of the labor judiciary in Brazil has been gradually changing face, a scenario that was predominantly male, is giving way to a process of feminization and juvenization that has expanded within the Justice, mainly in labor courts.

O nosso objetivo foi investigar as condições de produção da justiça do trabalho no Brasil e seus impactos na saúde da magistratura trabalhista no período de 2003 a 2014, período que marca o início da Emenda Constitucional nº45/2004, que provocou significativas mudanças no Poder Judiciário brasileiro, em especial, na Justiça do Trabalho, que teve sua competência ampliada, através da nova redação dada ao art.114 da Constituição Federal. Nesses dez anos de modernização do judiciário, modernização conversadora permeada pela lógica empresarial, ocorreu à introdução de tecnologias informacionais-organizacionais, além do choque de gestão, que nada mais é que o processo judicial eletrônico acoplado a gestão toyotista. Nesse processo de transição, os magistrados de primeira instância da Justiça do Trabalho conseguiram relatar as dimensões da precarização do trabalho e da saúde através de entrevistas e coleta de dados empíricos. Com os dados, verificamos que o perfil da magistratura trabalhista no Brasil vem aos poucos mudando de face, um cenário que era predominantemente masculino, vem dando espaço para um processo de feminilização e juvenilização que tem se ampliado dentro da Justiça, principalmente na Justiça do Trabalho.
Keywords: Justiça do trabalho; Juízes; Processo eletrônico; Trabalho - Aspectos sociais; Work Social aspects